2020
DOI: 10.5339/qmj.2020.6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Progress of an ACGME-International Accredited Residency Program in Qatar

Abstract: Background: The American College of Physicians’ (ACP) Internal Medicine In-Training Examination (IM-ITE) is designed to evaluate the cognitive knowledge of residents to aid them and program directors in evaluating the training experience. Objective: To determine the impact of the curriculum reform accompanied by the Accreditation Council for Graduate Medical Education (ACGME)-I alignment and accreditation on the internal medicine residency program (IMRP) using residents’ performance in the ACP's ITE from 2008 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Adherence to the ACGME-I rules among HMC residents has previously been associated with improved examination and research performance. 32 , 33 The same finding was recorded in the present study, as residents reported more time for studying, exam preparations, and research activities with the 12-hour on-call system. On the other hand, Nevin et al found that the implementation of the AGMCE duty hours rule was associated with fewer hours spent in the hospital, which inevitably decreased hands-on clinical education.…”
Section: Discussionsupporting
confidence: 86%
“…Adherence to the ACGME-I rules among HMC residents has previously been associated with improved examination and research performance. 32 , 33 The same finding was recorded in the present study, as residents reported more time for studying, exam preparations, and research activities with the 12-hour on-call system. On the other hand, Nevin et al found that the implementation of the AGMCE duty hours rule was associated with fewer hours spent in the hospital, which inevitably decreased hands-on clinical education.…”
Section: Discussionsupporting
confidence: 86%
“…Expatriates constitute a significant portion of Qatar’s total population, playing a vital role in the country’s healthcare system, which boasts prestigious Joint Commission International (JCI) and Accreditation Council for Graduate Medical Education-International (ACGME-I) accreditations [ 8 ]. The presence of expatriates in Qatar’s healthcare system is crucial because they fill essential roles, provide specialized services, and bring a global perspective to medical and patient care practices [ 9 ].…”
Section: Introductionmentioning
confidence: 99%